SEJARAH MUSIK MAK YONG PADA MASYARAKAT DAYAK SALAKO - Oktavianus, Riksi; Istiandini, Winda; Muniir, Asfar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study was backgrounded by the lack of documentation for a cultural reservation. The formulation of this study is (1) the history of Mak Yong Music in Salako Dayak society of Bagak Sahwa Village, Singkawang Timur District of Singkawang City, and (2) the elements of cultural acculturation between Dayak and Melayu in Mak Yong music. This study was conducted with the descriptive method in the form of qualitative, using a historical approach. The data collection was done using observation, interview,and documentation techniques. The data were validated using the triangulation technique.Mak Yong music was created since the 1950s by both the people of Dayak Salako Tribe and Malay tribes in Selakau. The music was officially recognized in 1967s a Gawai Padi event which was held at the Bagak Sahwa village. The music was performed as a part of the events led by Nek Jogong. In 1952, the system has changed, that is, people had to use tickets in the form of handkerchiefs. This study is hoped to be contributive by implementing the materials into the Arts and Cultures subject in Class VIII in the first semester.Keywords: Development and Acculturation History, Mak Yong Music